WITHDRAWN: Characterising residual stresses in a dissimilar metal electron beam welded plate. (February 2020) - Venkata, K.A.; Truman, C.E.; Smith, D.J.; Bhaduri, A.K.
Abstract : This article has been withdrawn at the request of the author(s) and/or editor. The Publisher apologizes for any inconvenience this may cause. The full Elsevier Policy on Article Withdrawal can be found at http://www.elsevier.com/locate/withdrawalpolicy .